Relationship between Thyroid autoantibodies, imbalance of some essential Trace elements in the pathology of simple nontoxic Goitre (2016)
Autoimmunity and certain micronutrients have been implicated in the pathogenesis of thyroid disorders such as simple nontoxic goitre (SNTG). Alterations in certain trace elements and autoimmune parameters may arise from an indeterminate autoimmune mechanism. We sought to evaluate the association and interactions between trace elements and autoantibodies in simple nontoxic goitre. All consenting participants based on clinical and thyroid function tests were recruited for this case-control study. Subjects comprised of 37 patients and 44 controls, from the Surgery Outpatient and Endocrinology Clinics of the University College Hospital and the Lagos University Teaching Hospital, respectively. Anthropometric indices were measured, serum trace element were determined using atomic absorption spectrophotometer (AAS), thyroid autoantibodies and thyroid function tests were performed in serum using Enzyme linked immunosorbent assay (ELISA). Thyroperoxidase and thyroglobulin antibodies were significantly elevated in SNTG compared with controls, suggesting immune alteration. The free triiodothyronine (FT3) and free thyroxine (FT4) were significantly increased in SNTG (3.72±0.02 and 14.9±0.21 pmol/L) compared with controls (3.63±0.12. pmol/L and 13.12±0.12 pmol/L). The level of TSH was significantly increased in SNTG compared with controls. Antithyroglobulin level was positive in 14.0% (130.93±35.02 kiu/L) SNTG. Significantly reduced levels of Cu (11.92±0.32, µmol/L), Fe (20.13±0.52µmol/L) and Se (0.53±0.01µmol/L) relative to the controls (16.12±0.22, 28.73±0.23 and 3.82±0.03µmol/l) were found in SNTG. Simple nontoxic goitre appear to be associated with imbalance in certain essential trace elements and presence of autoantibodies which probably are among the key mechanisms involved in the pathology of thyroid disorders. Early detection of these abnormalities may be useful in the better understanding and improved management of thyroid disorders.